Asymptomatic Endometrial Thickening of 8 mm or Greater on Postcontrast Computed Tomography in Postmenopausal Women Is a Predictor of Endometrial Cancer. Issue 1 (January 2019) - Franconeri, Andrea; Fang, Jieming; Brook, Alexander; Brook, Olga R.
Abstract : Objectives: The aim of this study was to assess the value of opportunistic endometrial thickness measurement on postcontrast computed tomography (CT) as a predictor of endometrial cancer in asymptomatic postmenopausal women. Methods: For this Health Insurance Portability and Accountability Act–compliant, institutional review board–approved retrospective study with waiver of informed consent, our institution's tumor board database was searched for postmenopausal patients, diagnosed with endometrial cancer between August 2003 and December 2016 and who had a postcontrast pelvic CT within 12 months prior to the cancer diagnosis (while they were asymptomatic)—"cancer group." Same number of age-matched patients who had postcontrast pelvic CT constituted the noncancer control group. Endometrial thickness was measured on sagittal postcontrast CT images. Results: After applying exclusion criteria, 22 asymptomatic patients who were diagnosed with endometrial cancer within 1 year after the CT comprised the cancer group, and 22 age-matched patients comprised the control group. Average endometrial thickness was 18.7 ± 14.8 mm (range, 2–70 mm) in the cancer group and 3.6 ± 2.5 mm (range, 1.8–10 mm) in the control group ( P < 0.0001). Endometrial thickness 8 mm or greater predicted endometrial cancer with 86% sensitivity and 91% specificity in these asymptomatic patients. Area under the receiver operating characteristic curve for endometrial thickness as a predictor of endometrial cancer was 0.92. Conclusions: Endometrial thickness 8 mm or greater on sagittal postcontrast CT was shown to have high sensitivity in opportunistic detection of endometrial cancer in asymptomatic postmenopausal women.